PENGARUH GOOD CORPORATE GOVERNANCE (GCG)TERHADAP KINERJA KEUANGAN PERUSAHAAN: Studi Empiris Per usahaan Manufaktur Sub Sektor Farmasi yang terdaftar Di Bursa Efek Indonesia Tahun 2017-2018 (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
Economic developments in the business world are very fast and increasingly strong, resulting in demands for companies to continue to carry out various kinds of innovations to improve performance and expand company businesses so that they are able to compete and survive in the business world. Research with the title "The Influence of Good Corporate Governance (GCG) on Company Financial Performance”. This research uses a population of pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2018 period. The purpose of this research is to examine the influence of Institutional Ownership on Company Financial Performance, to examine the influence of Managerial Ownership on Company Financial Performance and to examine the influence of Institutional Ownership and Managerial Ownership on Company Financial Performance. The data sources used are secondary data and a purposive sampling method to determine the sample. will be used and produce a final sample of 10 manufacturing companies. After carrying out the sampling criteria, 6 companies were used as samples. The data in this research were analyzed using the SPSS program. The analysis used was descriptive analysis, classical assumption testing, statistical analysis and hypothesis testing. Based on the data analysis carried out, it was concluded that institutional ownership had a positive effect on financial performance, managerial ownership had no significant effect on financial performance, institutional ownership and managerial ownership had a positive effect on financial performance.